KONDISI HABITAT HUTAN MANGROVE DI DESA MEMBUKE KECAMATAN POSO PESISIR UTARA KABUPATEN POSO - Artana, I Wayan Budi; Korja, I Nengah; Ramlah, Sitti (ForestSains, 2016)
The purpose of this research was to determine the condition of mangrove forest habitat in Membuke village, Poso Pesisir Utara District, Poso regency.Â  The method of this research is descriptive. The location for sampling soil was determined by purposive sampling method. Based on field observations, it was found that there were four types of stands, namely Rhizophora apiculata, Sonneratia alba, Avicennia marina and Xylocarpus granatum. Soil samples were taken at each of stands and analyzed in Laboratory of agricultural faculty, Tadulako University. The results of the research in the field and on the analysis of eight parameters observed showed that soil pH ranged from 5.33 to 6.29, the dominant soil color is black. soil texture from the four observation points was dominated clayey loam to sandy clay, the salinity ranged 26,9 ppt to 31,6 ppt, water pH ranged from 5.93 to 6.52, Nitrogen (N-total) ranged 0.33% to 0.39%, Phosphorus (P-total) ranged 25.72 (mg / 100g)Â  to 53.76 (mg / 100g). The KTK value ranged 15,20 to 28.76 (cmol (+) kg-1). The depth of the mud in the mangrove forests in four different observation site were different, in which the depth of mud under Rhizophora stand was 45 cm, under Rhizophora was 30 cm, under avicenia marinna stand was 41 cm, and under Xylicarpur Granatum stands have very deep mud that was 143 cm.